Micro, Small, and Medium Enterprises (MSMEs) : The Current Scenario - Sudarsana Murthy, D.; Narasaiah, P. V. (Arthshastra Indian Journal of Economics & Research, 2017)
Micro, small and medium enterprises have contributed significantly to the industrial development in the country, particularly in the rural sphere. They have added distinctly to the output and also to the employment generation in our country. The country is endowed with abundant natural, mineral, and agro-based resources, which have potential for industrial development, particularly small scale industrial development. In the MSME sector, a majority of the small units are facing sickness. In spite of many efforts made to boost industrial development, there has not been as much industrialization as desired. In order to build a proper and effective strategy for the development of our country's economy through the MSME sector, some of the important strategies could be motivating and changing of the mindset and attitude of the local youth for taking up various entrepreneurial ventures. The present study reviewed the growth and development of MSMEs in the country in general and Andhra Pradesh in particular. It also examined the development of MSMEs during the Five - Year Plans. The study also suggested feasible measures for effective functioning of MSMEs in the country with particular reference to the state of Andhra Pradesh. The study was based upon secondary data. The analysis of the data and application of appropriate statistical tools helped largely in drawing meaningful and useful inferences.